2015
DOI: 10.17221/8530-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against burn-induced hepatic oxidative injury by inducing HO-1 via the Nrf2 pathway

Abstract: Melatonin exerts beneficial effects on early liver injury by modulating hepatic oxidative stress. In order to understand the protective effect of melatonin against burn-induced hepatic injury we investigated the expression of 4-hydroxynonenal (4-HNE), a main product of lipid peroxidation and mediator of oxidative injury, the inducible heme-oxygenase-1 (HO-1), an antioxidant enzyme, and the anti-oxidative stress regulator erythroid 2-related factor 2 (Nrf2) in a burn rat model. Expression and localisation of HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…One of the genes regulated through Nrf2 is heme oxygenase-1 ( HO-1 ). HO-1/Nrf2 have been shown to be involved in the protection of burn-induced hepatic oxidative injury, carbon tetrachloride-induced liver injury, nickel-induced DNA methylation, and inflammation ( 19 , 20 ). Nrf2 also plays a critical role in the mechanism of hepatic IR injury and is considered a potential therapeutic target for preventing hepatic IR injury during liver surgery ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the genes regulated through Nrf2 is heme oxygenase-1 ( HO-1 ). HO-1/Nrf2 have been shown to be involved in the protection of burn-induced hepatic oxidative injury, carbon tetrachloride-induced liver injury, nickel-induced DNA methylation, and inflammation ( 19 , 20 ). Nrf2 also plays a critical role in the mechanism of hepatic IR injury and is considered a potential therapeutic target for preventing hepatic IR injury during liver surgery ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have previously demonstrated that GHP protected cellular damage by up-regulating the activities of SOD, CAT and GSH-Px in H 2 O 2 -stressed RAW 264.7 macrophages. Among the various cytoprotective enzymes, HO-1 can confer cytoprotection on a wide variety of cells against oxidative damage [ 35 ]. Moreover, HO-1 induction has been considered as a crucial beneficial mechanism to maintain homeostasis for the liver injury [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of Nrf2 has also been associated with the effects of melatonin in reducing oxidative and nitrosative DNA damage [ 312 ]. In fact, numerous investigations have shown that melatonin activates phase-2 antioxidative enzymes, via the Nrf2 pathway, including heme oxygenase-1 (HO-1), γ-glutamylcysteine synthetase (γ-GSC), nicotinamide adenine dinucleotide phosphate (NADPH): quinone dehydrogenase-1 (NQO1) and SOD [ 313 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 , 326 , 327 , 328 , 329 , 330 , 331 , 332 , 333 ].…”
Section: Antioxidant Protectionmentioning
confidence: 99%